2003
DOI: 10.1002/art.10873
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of furin‐like enzymes blocks interleukin‐1α/oncostatin M–stimulated cartilage degradation

Abstract: Objective. To investigate the role of furin-like enzymes in the proteolytic cascades leading to cartilage breakdown and to examine which collagenase(s) contribute to collagen degradation.Methods. Bovine nasal cartilage was stimulated to resorb with the addition of interleukin-1␣ (IL-1␣)/ oncostatin M (OSM) in the presence or absence of a furin inhibitor, Dec-RVKR-CH 2 Cl, or selective matrix metalloproteinase 1 (MMP-1) inhibitors. Collagen and proteoglycan levels were determined by assay of hydroxyproline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 76 publications
(91 reference statements)
4
44
0
Order By: Relevance
“…In a model of cartilage resorption, we have shown that the addition of a chloromethylketone PC inhibitor reduces the levels of aggrecan and collagen breakdown, thus implicating a role for PCs in the cascades leading to cartilage resorption (148). In this assay, a reduction in the levels of active collagenase and MMP-2 was observed, suggesting that PCs are involved in proMMP activation (see below).…”
Section: Pro-protein Convertases (Pcs)mentioning
confidence: 81%
See 2 more Smart Citations
“…In a model of cartilage resorption, we have shown that the addition of a chloromethylketone PC inhibitor reduces the levels of aggrecan and collagen breakdown, thus implicating a role for PCs in the cascades leading to cartilage resorption (148). In this assay, a reduction in the levels of active collagenase and MMP-2 was observed, suggesting that PCs are involved in proMMP activation (see below).…”
Section: Pro-protein Convertases (Pcs)mentioning
confidence: 81%
“…Although it is still too early to know whether distinct serine proteinase cascade(s) occur in RA and OA, it is evident that there is overlap in terms of collagenolysis (148,176,183). Further understanding of the complex roles of these enzymes, their substrate specificities, and identification of novel serine proteinases in the arthritic joint will provide new opportunities to identify tractable therapeutic targets that effectively prevent pathologic tissue turnover in RA and OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) have a furin recognition sequence between the propeptide and the catalytic domain and these enzymes are often activated within the Golgi. Recent data show that cartilage explant cultures, treated with cytokines and an inhibitor of furin, have reduced levels of active collagenases and low collagen release (Milner et al 2003). For those MMPs without a furin site, the proteolytic removal of the propeptide is likely to be achieved in a tightly controlled environment close to the cell surface.…”
Section: Activation Of Proenzymesmentioning
confidence: 98%
“…The assay using the coumarin-labeled peptide substrate has been in popular use for HTS; however, the other estimation of inhibitors should be needed to confirm the inhibition of collagenase activity using the native substrate, because the labeled peptide substrate has different characteristics from the native one. At the second stage, the drug candidates that have passed through the first stage need to be checked for whether they can inhibit the cleavage of triple-helical collagen by collagenase, using sodium dodecylsulfate-polyacrylamide gel electrophoresis [6], zymography [7][8][9] and collagenolysis assay [10][11][12] with native, fluorescence-labeled or radioisotope-labeled collagen as a substrate. However, these assays have drawbacks such as troublesome procedure and poor quantification.…”
Section: Introductionmentioning
confidence: 99%